Status and Potential of the Peroryctidae Family to Improve Food Security in Papua New Guinea - David Lopez Cornelio (Jurnal Manajemen Hutan Tropika, 2010)
As the importance and threats of wildlife resources in Melanesia are widely recognized, their appropriate use is critical to achieve sustainable development in the country. An underestimated relationship between the status of the species with forest condition and food security is discussed. Being as nutritious as conventional imported red meats, bandicoots are also considered as the most rapidly breeding marsupial. The taxonomy, morphology, habitat, and reproductive characteristics of the family Peroryctidae (bandicoots) are succinctly described in order to elucidate the species potential in continuous controlled harvests in the wild and its eventual farming, until now successful abroad with one species from a related family. This effort requires the application of proper regulations that guarantee continuous harvests in accordance to the population dynamics.